Deception Techniques as Communication Strategies of Cheating Spouses - Amalia Dewi (Journal of Social Research, 2025)
Marital infidelity has become increasingly prevalent, often leading to the destruction of marriages and families when discovered. However, some individuals successfully conceal their affairs through strategic deception. This qualitative study explores the communication strategies employed by cheating spouses to hide their infidelity. Using a phenomenological approach, data were collected through in-depth interviews with five individuals (three men and two women in their 30s) engaged in long-term extramarital affairs without being caught. Turner's typology of deception—lies, exaggeration, half-truths, secrets, and diversion—served as the conceptual framework. The findings revealed that all informants utilized these deception types to mislead their spouses, with lies being the most common tactic. Half-truths and diversion were also frequently employed to avoid suspicion. The study highlights the manipulative behaviors and psychological dynamics underlying these strategies, suggesting a potential link to narcissistic traits. The research contributes to the understanding of deceptive communication in marital relationships and underscores the need for further studies on protective communication factors to mitigate infidelity's harm.